"It is always going to change" – examining the experiences of managing top-down changes by sport development officers working in national governing bodies of sport in England. Issue 1 (4th March 2021) - Thompson, Anne; Bloyce, Daniel; Mackintosh, Chris
ABSTRACT: Research question: This article examines how sport development officers (SDOs) employed within national governing bodies of sport (NGB) managed Sport England's top-down policy changes from 2008 to 2015. The main research question examines the experiences of SDOs as they responded to, and managed these changes at the community level. Research methods: In-depth, semi-structured interviews gathered qualitative data from 18 employees from four NGBs, including 6 SDOs, Chief Executive Officers (CEOs), senior managers and a representative from Sport England, with responsibility for policy formulation. Results and Findings: SDOs felt increasingly constrained in how they worked due to the intensification of a top-down and cyclical process of change, a result-orientated approach and the sporting habitus of SDOs. These factors combined to create resistance among some SDOs as the power differentials within the interdependencies formed, which contributed to the unintentional outcome of elongating the time taken to implement policy on the ground. Implications: This article has developed more object-adequate insights into how SDOs have responded to, and managed top-down policy implementation. The article suggests recommendations for policy-makers, Sport England and NGBs, to consider the dynamic interdependencies in which employees are bound and a more rounded and processual view to policy formulation and implementation